The influence of the competence of central and regional financial analysts on the quality of human resources in regional revenue and expenditure budget (APBD) planning and budgeting in serdang bedagai regency - Mhd Zuchry Hidayat Kemit; Fajar Pasaribu (Economic: Journal Economic and Business, 2026)
This study aims to analyze the influence of central and regional financial analyst competency on the quality of human resources in the planning and budgeting of the Regional Revenue and Expenditure Budget (APBD) in Serdang Bedagai Regency. This study uses a quantitative approach with a survey method by distributing questionnaires to 50 civil servants involved in the regional planning and budgeting process. The data obtained have been tested for quality through validity and reliability tests and have met the required classical assumptions. Data analysis was performed using simple linear regression. The results show that the competency of central and regional financial analysts has a positive and significant effect on the quality of human resources in APBD planning and budgeting. The coefficient of determination value indicates that the competency of financial analysts is able to explain most of the variation in human resource quality, while the remainder is influenced by other factors outside the study. Thus, improving the competency of financial analysts is proven to contribute to improving the quality of regional planning and budgeting.